2019
DOI: 10.1186/s13567-019-0665-8
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 5-mediated IL-17C expression in intestinal epithelial cells enhances epithelial host defense against F4+ ETEC infection

Abstract: Enterotoxigenic Escherichia coli (ETEC) are an important cause of post-weaning diarrhea (PWD) in piglets. The IL-17 cytokine family is well known to play important roles in the host defense against bacterial infections at the mucosa. Previously, we reported the potential role of IL-17A in clearing an ETEC infection in piglets. IL-17C, another member of the IL-17 family, is highly expressed in the intestinal epithelium, however, its role during an ETEC infection is still unclear. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…To address if these monolayers allow adherence of ETEC as shown in traditional cell culture using porcine intestinal epithelial cell lines, like IPEC-J2 [ 9 , 35 ], confluent enteroid monolayers isolated from jejunum or ileum were inoculated with a wildtype F4-fimbriated ETEC strain or an F4-deficient isogenic mutant strain. As shown in Figure 4 , both jejunal (Figure 4 A) and ileal enteroid monolayers (Figure 4 B) supported F4-mediated adhesion of ETEC bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…To address if these monolayers allow adherence of ETEC as shown in traditional cell culture using porcine intestinal epithelial cell lines, like IPEC-J2 [ 9 , 35 ], confluent enteroid monolayers isolated from jejunum or ileum were inoculated with a wildtype F4-fimbriated ETEC strain or an F4-deficient isogenic mutant strain. As shown in Figure 4 , both jejunal (Figure 4 A) and ileal enteroid monolayers (Figure 4 B) supported F4-mediated adhesion of ETEC bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The deletion of flic , a gene encoding the major flagellin protein, resulted in abnormal growth and decreased motility and biofilm formation of bacteria, such as Edwardsiella tarda , Cronobacter malonaticus (G361, O:2), and F18 enterotoxigenic E. coli (ETEC) (F107/86, O139:H1:F18ab) (Duan et al 2012 ; He et al 2012 ; Ling et al 2021 ). Previous studies have shown that flagellin also contributes to probiotic effects and has emerged as an immune modulator to affect the interaction between bacteria; these responses were closely associated with the flagellin concentration and the monomer-specific structural features (Duan et al 2012 ; Lebeer et al 2010 ; Luo et al 2019 ; Rossez et al 2015 ).…”
Section: Flagellin Is the Specific Ligand For Tlr5 Recognition And Provides Beneficial Immunomodulatory Property To The Hostmentioning
confidence: 99%
“…TLR5 can recognize extracellular flagellin and utilize MyD88 to initiate MAPK signaling and NF-κB activation, stimulating cytokine secretion and eliciting an inflammatory response to eliminate pathogens (Hajam et al 2017 ; Ramos et al 2004 ). For instance, the flagellin of F4 ETEC (C83901, O8:K87: F4ab) induces TLR5-mediated IL-17C expression in intestinal epithelial cells and increases antimicrobial peptides and tight junction protein expression in an autocrine/paracrine manner to promote the mucosal host defense against bacterial infection (Luo et al 2019 ). Simultaneously, a low expression of TLR5 will suppress the immune response to ETEC infection and reduce cell damage in the intestine (Dai et al 2019 ).…”
Section: Flagellin Is the Specific Ligand For Tlr5 Recognition And Provides Beneficial Immunomodulatory Property To The Hostmentioning
confidence: 99%
“…According to recent reports, IL-17 exerts anti-inflammatory effects in the intestine by regulating the secretion of secretory immunoglobulin A (sIgA). IL-17 promotes the secretion of chemokines, such as CXCL1, CXCL2, and CCL20, in a positive feedback way to recruit neutrophils to enhance inflammatory responses [68,69].…”
Section: Zinc Plays An Important Role In the Host-pathogenic Bacteriamentioning
confidence: 99%